1997
DOI: 10.1172/jci119752
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II inhibits insulin signaling in aortic smooth muscle cells at multiple levels. A potential role for serine phosphorylation in insulin/angiotensin II crosstalk.

Abstract: To investigate potential interactions between angiotensin II (AII) and the insulin signaling system in the vasculature, insulin and AII regulation of insulin receptor substrate-1 (IRS-1) phosphorylation and phosphatidylinositol (PI) 3-kinase activation were examined in rat aortic smooth muscle cells. Pretreatment of cells with AII inhibited insulin-stimulated PI 3-kinase activity associated with IRS-1 by 60%. While AII did not impair insulin-stimulated tyrosine phosphorylation of the insulin receptor (IR) ␤ -s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
297
5
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(325 citation statements)
references
References 72 publications
13
297
5
5
Order By: Relevance
“…Consistent with a negative feedback role, we observed that the overexpression of PKC-significantly impaired insulin-stimulated tyrosine phosphorylation of IRS-1. These results are in keeping with studies showing that increased serine phosphorylation of IRS-1 secondary to other stimuli is accompanied by impairment in the ability of IRS-1 to undergo tyrosine phosphorylation after insulin stimulation (15)(16)(17)(18)(19)(20)(21)(22)43). In addition, there was some specificity to the impairment of IRS-1 function because the interaction between IRS-1 and SHP-2 appeared to be unaffected by the overexpression of PKC-.…”
Section: Irs-1 May Be a Novel Physiological Substrate For Pkc--supporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with a negative feedback role, we observed that the overexpression of PKC-significantly impaired insulin-stimulated tyrosine phosphorylation of IRS-1. These results are in keeping with studies showing that increased serine phosphorylation of IRS-1 secondary to other stimuli is accompanied by impairment in the ability of IRS-1 to undergo tyrosine phosphorylation after insulin stimulation (15)(16)(17)(18)(19)(20)(21)(22)43). In addition, there was some specificity to the impairment of IRS-1 function because the interaction between IRS-1 and SHP-2 appeared to be unaffected by the overexpression of PKC-.…”
Section: Irs-1 May Be a Novel Physiological Substrate For Pkc--supporting
confidence: 89%
“…IRS-1 is also extensively phosphorylated on serine residues, and modulation of IRS-1 serine phosphorylation is observed in response to the treatment of cells with a variety of agents, including insulin (13,14), tumor necrosis factor ␣ (15-17), PDGF (18), angiotensin II (19), phorbol esters (20,21), and okadaic acid (14,22). Interestingly, IRS-1 has recently been identified as a substrate for both Akt and GSK-3, Ser/Thr kinases downstream from PI 3-kinase that participate in the metabolic actions of insulin (23,24).…”
Section: Pkc-mentioning
confidence: 99%
“…The main player in this connection is Ang II acting through the AT1R (Velloso et al 2006, Folli et al 1997, Jandeleit-Dahm et al 2005. This correlates well with the beneficial effect of Ang II receptor type 1 (AT1R) blockers (e.g.…”
Section: Introductionmentioning
confidence: 70%
“…IRS-1 degradation has been extensively studied in insulin-sensitive cell types, such as adipocytes and skeletal muscle cells and also in these tissues in animal models (13,31,(42)(43)(44). Hyperglycemia-induced IRS-1 down-regulation has been shown in vascular smooth muscle following PKC activation (45), ␤-adrenergic stimulation (46), and angiotensin II exposure (47,48). Exposure to growth factors, including IGF-I, also enhances IRS-1 degradation in a variety of cells (25,26,49,50).…”
Section: Discussionmentioning
confidence: 99%